Penerapan Media Schoology untuk Meningkatkan Motivasi dan Hasil Belajar Siswa dalam Pembelajaran Bahasa Indonesia di SMP Negeri 3 Bojong Pekalongan - Waginah Dwi Nuryaningsih (Jurnal Paedagogy, 2021)
This study aims to analyze the increase in motivation and student learning outcomes in learning Indonesian using schoology media assisted by the WhatsApp application. This research method used quasi-experimental with pretest-posttest control group design. The research sample consisted of class VIII A as the experimental class implementing Distance Learning with schoology media assisted by the WhatsApp application and class VIII B as the control class without using schoology media. Data collection techniques with knowledge competency tests, questionnaires, and interviews. Meanwhile, the data analysis technique used in this research was quantitative and qualitative descriptive analysis. The results of this study indicate that the competence of news text knowledge in the experimental class using schoology media is better than without using schoology media. The average learning outcomes obtained were 81, the average N-gain obtained was 0.72 in good category. So it can be concluded that there is an increase in student motivation and learning outcomes in learning Indonesian.